Organizational excellence as the driver for organizational performance: A study on Dubai Police - Al-Dhaafri, Hassan Saleh; Yusoff, Rushami Zien; Al-Swidi, Abdullah Kaid (2014)
This study was set up to examine the effect of organizational excellence on organizational performance.A questionnaire survey was employed to collect the data from Dubai Police departments. Two hundred and fifty questionnaires were distributed and hundred and seventy five were returned completely. To analyze the data collected, Partial Least Square (PLS) structural Equation Modelling was employed.Based in the statistical results, the effect of organizational excellence on organizational performance was confirmed. The results of this study have different theoretical and practical implications. Theoretically, this study fill the gap in the previous literature in terms of the few studies examine empirically the casual effect of organizational excellence on organizational performance in public organization.Practically, this study will increase the awareness on managers, decision makers, and practitioners about the significant of excellence when implementing their strategies and practices.